Nodal downstaging in esophageal and esophagogastric junction cancer: more important than ever - Zanoni, Andrea (Journal of Thoracic Disease, 2017)
Esophageal and esophagogastric junction cancers are still highly deadly malignancies. Nonetheless, multimodal approaches improved survival and gave clinicians some more weapons and patients some more hope. Multimodal approaches include surgery as the mainstay of treatment, together with chemotherapy (ChT) and radiotherapy (RT). Different protocols of associations of ChT and RT have been proposed, but now the most accepted approach considers induction, also called neoadjuvant, treatment with concurrent chemoradiotherapy (CRT) followed by surgery for squamous cell carcinoma and Siewert type I and II adenocarcinoma.